Pagan Britain - Hutton, Ronald (New Haven : Yale University Press, 2013)
Britain's pagan past, with its astonishing number and variety of mysterious monuments, atmospheric sites, enigmatic artefacts, bloodthirsty legends and cryptic inscriptions, has always enthralled and perplexed us. 'Pagan Britain' is a history of religious beliefs from the Old Stone Age to the coming of Christianity. This ambitious book integrates the latest evidence to survey our transformed - and transforming - understanding of early religious behaviour; and, also, the way in which that behaviour has been interpreted in recent times, as a mirror for modern dreams and fears. From the Palaeolithic era to the coming of Christianity and beyond, Hutton reveals the long development, rapid suppression and enduring cultural significance of paganism. Woven into the chronological narrative are numerous case studies of sacred sites both well-known - Stonehenge, Avebury, Seahenge and Maiden Castle - and more unusual far-flung locations across the mainland and coastal islands.
Description based on print version record.
Keywords: Great Britain -- Religion -- To 449.; Paganism -- Great Britain -- History; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Electronic books